Fluid Mechanics, SI Edition - Hibbeler, Russell C. (Pearson International Content, 2024)
Fluid Mechanics excels in providing a clear and thorough presentation of the theory and application of fluid mechanics principles. Drawing upon his decades of classroom experience and his knowledge of how students learn, Professor Hibbeler provides highly visual, methodical applications to help you conceptualize and master difficult concepts. A variety of problem types stress realistic situations encountered in the field, with several levels of difficulty to give you the practice you need to excel in your courses and career.